Use of adhesion agents in the granulation of seeds of creole corn with rock poder - Melo, Luan Danilo Ferreira de Andrade; Melo Junior, João Luciano de Andrade; Crisostomo, Natália Marinho Silva; Berto, Thaíse dos Santos; Ramos, Marcus Gabriel de Carvalho; Silva, Laís Gonzaga da (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Corn (Zea mays L.) is one of the most widely planted grains in the world, having a considerable role in the economy as it expresses high commercial value. Seed pelletizing is becoming a growing and prosperous technology, as it adds value to seeds and contributes to an increasingly strict and competitive market. Thus, the work aimed to evaluate the effect of different adherent agents on pelletizing and physiological potential of Creole corn seeds. The work was conducted at the Plant Propagation Laboratory belonging to the Engineering and Agricultural Sciences Campus of the Federal University of Alagoas. As the adhesive material was used: water, aloe vera, glue based on polyvinyl acetate (PVA), mandacaru extract, palm extract and manioc gum. No coating used or rock powder (MB-4). The parameters evaluated were: water content, weight of a thousand seeds, first germination count, germination, germination speed index, average germination time, germination uncertainty, average germination speed, length and dry mass of the root and aerial part. Cassava gum is the most efficient adherent agent in pelletizing corn seeds with rock powder.